2013
DOI: 10.9734/bbj/2013/3033
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gas Flaring on the Phytochemical and Nutritional Composition of Treculia africana and Vigna subterranean

Abstract: Aims:The effect of petroleum exploration and exploitation activities on the phytochemical and nutritional composition of African breadfruit (Treculia africana) and Bambara groundnuts (Vigna subterranean) harvested from polluted and unpolluted environment were studied. Study Design: Plant samples were collected from Izombe, an environment highly polluted by gas flaring and Eziobodo, an environment not known for gas flare exposures. Both locations are within the (Niger-Delta) rain forest region of Imo State, Nig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 21 publications
2
11
1
Order By: Relevance
“…One-Way ANOVA at P <0.05 gave F value (3380.66) > critical F value (2.534) showing that the proximate composition of the breadfruit samples varies significantly with the solvent type and drying method. The mean total ash content was 3.56% which is slightly higher than 2% (Ogunleye and Parakoyi, 1992), 1.2% (Dalziel, 1937), 2.80% (Nwabueze and Uchendu, 2011) and 2.13% (Ujowundu et al, 2013) recorded as ash contents in breadfruit samples of similar researches and comparable to 3.24 reported by Akubor and co-workers (Akubor et al, 2000). The ash content indicates the nutritional value and product quality of food (Kirk and Sawyer, 1998).…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…One-Way ANOVA at P <0.05 gave F value (3380.66) > critical F value (2.534) showing that the proximate composition of the breadfruit samples varies significantly with the solvent type and drying method. The mean total ash content was 3.56% which is slightly higher than 2% (Ogunleye and Parakoyi, 1992), 1.2% (Dalziel, 1937), 2.80% (Nwabueze and Uchendu, 2011) and 2.13% (Ujowundu et al, 2013) recorded as ash contents in breadfruit samples of similar researches and comparable to 3.24 reported by Akubor and co-workers (Akubor et al, 2000). The ash content indicates the nutritional value and product quality of food (Kirk and Sawyer, 1998).…”
Section: Resultsmentioning
confidence: 79%
“…The crude fibre contents (1.04-1.31%) are appreciable and it has been reported that consumption of diet rich in fibre can reduce the incidence of colon cancer and antherosclerosis since they lower blood cholesterol level (Hamilton and Bhati, 2003;Ujowundu et al, 2013). In addition, the mean protein content of the samples was 12.28% which is comparable to 13.56% (Nwabueze and Uchendu, 2011), 13.07% (Ujowundu et al, 2013) but lower than 18.17% (Oyenuga, 1968) recorded as protein content of breadfruit samples in related studies.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Ifemeje [82] reported gas flaring could change the anti-nutrient compositions (alkaloid, phytate, oxalate, Saponin, tannin and cyanogenic glycosides) in some common vegetables used for food purposes such as scent leaf, bitter leaf, water leaf and fluted pumpkin leaf. Ujowundu et al [83] also reported impacts in phytochemical (alkaloid, tannin, cyanogenic glycoside, phytate), proximate composition (moisture, ash, protein and carbohydrate), micronutrients (calcium, sodium, magnesium, potassium and phosphorus) and vitamins (riboflavin, vitamin E and C) in African breadfruit and Bambara groundnuts planted close to gas flaring stack. Anacletus et al [84] also reported that phytochemical (alkaloids, flavonoids, saponins and tannins) and trace metal (iron, lead, cadmium and zinc) constituents of fluted pumpkin could be affected by gas flaring.…”
Section: Impact On the Vegetationmentioning
confidence: 99%
“…This implies abundant energy for domestic and industries uses. However, due to poor and outdated technology and/or poor investment on modern technology great percentage of gas reserves are flared as waste during crude oil exploration and exploitation by petroleum industries operating in Nigeria [1,2]. Also industrialization has led to the pollution of aquatic and terrestrial environment [3].…”
Section: Introductionmentioning
confidence: 99%
“…The routes of exposure to PAHs are from inhalation of ambient and indoor air, exhaust fumes or ingestion of food [1,2,7,8]. PAHs, notably benzo(a)pyrene (BaP) have been reported to disturb the antioxidant defense system and it is also responsible for the induction of oxidative stress [9].…”
Section: Introductionmentioning
confidence: 99%